ANALYSIS OF METASTASES AND SURVIVAL RATES IN PATIENTS WITH UVEAL MELANOMA - S. V. Saakyan; T. V. Shirina (Опухоли головы и шеи, 2015)
Thirty-six cases of metastatic dissemination were analyzed in detail in patients with uveal melanoma after treatment. The onset time and risk factors of metastatic spread after different treatment options for uveal melanoma are given.